2022
DOI: 10.1111/joim.13541
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation for Parkinson's disease

Abstract: Parkinson's disease (PD) is a progressive neurodegenerative illness with both motor and nonmotor symptoms. Deep brain stimulation (DBS) is an established safe neurosurgical symptomatic therapy for eligible patients with advanced disease in whom medical treatment fails to provide adequate symptom control and good quality of life, or in whom dopaminergic medications induce severe side effects such as dyskinesias. DBS can be tailored to the patient's symptoms and targeted to various nodes along the basal ganglia–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 127 publications
0
34
1
1
Order By: Relevance
“…This study has several limitations. The primary effect of STN DBS is on motor symptoms of PD patients (Hariz and Blomstedt, 2022). In the present study, we assessed basic motor function by using the simple reaction task and found no effect of DBS-STN on it.…”
Section: Discussionmentioning
confidence: 50%
“…This study has several limitations. The primary effect of STN DBS is on motor symptoms of PD patients (Hariz and Blomstedt, 2022). In the present study, we assessed basic motor function by using the simple reaction task and found no effect of DBS-STN on it.…”
Section: Discussionmentioning
confidence: 50%
“…Electrical stimulation of the subthalamic nucleus (STN) is an established clinical therapy for reducing motor deficits associated with PD (Benabid et al 2009 ; Hariz and Blomstedt 2022 ), and the STN is considered a potential element in BG connections to the cerebellum. None of our cases labeled more than a few cells in STN, and it is likely that the effects of STN stimulation are mediated by its projections to GPi and SNr.…”
Section: Discussionmentioning
confidence: 99%
“…The patient walks now with great difficulty, and unable any longer to support himself with his stick, he dares not venture on this exercise, unless assisted by an attendant, who walking backwards before him, prevents his falling forwards, by the pressure of his hands against the fore part of his shoulders.' PD is a neurodegenerative disorder that generates both motor dysfunctions as well as other symptoms such as depression, pain, constipation, sleep disorders, cognitive decline and autonomic dysfunction [55]. The cardinal mo-tor symptoms of PD are tremor, ridigity, akinesia (both bradykinesia, slowness of movements, and hypokinesia, small amplitude of movement) and postural instability.…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…Dopamine is a neurotransmitter used in the motor circuitry and with its depletion, the projections from the SN to striatum will start to degrade. [55] The symptoms of PD are first treated with levodopa, a dopamine precursor that can cross the blood-brain barrier, and converts to dopamine in the brain [55,58]. In the beginning, this treatment can often satisfactorily control the PD symptoms but with the progression of the disease, many patients experience motor fluctuations from variations in dopamine levels and levodopa-induces dyskinesias (involuntary movements).…”
Section: Parkinson's Diseasementioning
confidence: 99%
See 1 more Smart Citation